Faktor Pemicu Pernikahan Dini Di Jorong Koto Tangah Kenagarian Koto Lamo Kecamatan Kapur Ix Kabupaten Lima Puluh Kota - Hidayati Suhaili; Dasril Afdal (IJOCE: Indonesia Journal of Civic Education, 2020)
The purpose of this research is to determine the factors that influence the occurrence of early marriage in Jorong Koto Tangah Kenagarian Koto Lamo, Kapur District IX, Lima Puluh Kota Regency. The study was conducted at Jorong Koto Tangah Kenagarian Koto Lamo Kapur District IX. This research is descriptive research. The informants of this research are where adolescents who engage in early marriage and parents of guardian nagari informants, religious leaders. Data collection techniques with field studies, interviews, depth and observation. Field data can then be analyzed and arranged in the form of tables and question and answer between clear researchers and qualitatively data analysis techniques using the techniques proposed by Milles and Hubermen and the steps of data collection, data reduction, data presentation, drawing conclusions. The results showed that: Factors that trigger early marriage in Jorong Koto Tangah Kenagarian Koto Lamo (1) Own desires, (2) Family factors, (3) Environmental influences, (4) Educational factors, (5) Family economic level factors. The conclusion of this research is the influence of parents, family economic level, environmental factors and promiscuity. Keywords : Early marriage